2022
DOI: 10.3390/nu14204403
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Healthy Eating Index-2010 and Incident Non-Communicable Diseases: Findings from a 15-Year Follow Up of Women from the 1973–78 Cohort of the Australian Longitudinal Study on Women’s Health

Abstract: Non-communicable diseases (NCDs) and multimorbidity (≥two chronic conditions), are increasing globally. Diet is a risk factor for some NCDs. We aimed to investigate the association between diet quality (DQ) and incident NCDs. Participants were from the Australian Longitudinal Study on Women’s Health 1973–78 cohort with no NCD and completed dietary data at survey 3 (2003, aged 25–30 years) who responded to at least one survey between survey 4 (2006) and survey 8 (2018). DQ was measured by the Alternative Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 133 publications
(196 reference statements)
0
14
1
Order By: Relevance
“…Reduced odds of asthma symptoms were documented in two French cohort studies (84,85) . In our repeated cross-sectional study, we found that women in the highest AHEI-2010 quintile had a 25 % reduction in the odds of asthma at 3 years after diet measurement (27) . By contrast, no association between the AHEI-2010 and adult-onset asthma had been reported (86,87) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduced odds of asthma symptoms were documented in two French cohort studies (84,85) . In our repeated cross-sectional study, we found that women in the highest AHEI-2010 quintile had a 25 % reduction in the odds of asthma at 3 years after diet measurement (27) . By contrast, no association between the AHEI-2010 and adult-onset asthma had been reported (86,87) .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, no association between the AHEI-2010 and adult-onset asthma had been reported (86,87) . These mixed findings could be partly explained by the application of different measures for asthma (77) such as continuous scoring variable (84,85) or diagnosis status (12,27,86) or present asthma condition (87) , and for measures of diet such as FFQ (12,27,84,86) or 24-h recalls (85,87) . However, the evidence of DQ in adults could be expanded by longitudinal analysis using GEE approach, especially lagged model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations